Grain Sorghum Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2003)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in south central Kansas.
MF575_2003_10
Keywords: MF575; Economics; Crops; MF